"Fractivism" in the City: Assessing Defiance at the Neighborhood Level. (June 2017) - Fisk, Jonathan M.; Park, Yunmi; Mahafza, Zachary
New extraction processes have unleashed an oil and gas renaissance. The boom has expanded employment opportunities and swelled state and local budgets. The renaissance, however, has a darker side. Environmentalists argue that it harms the environment, hastens the deterioration of infrastructure, and inconveniences citizens. While states may enjoy the majority of economic benefits, many of its costs are felt locally. For some residents, these costs are enough to fuel defiance. Two such examples are Denton, TX, and Longmont, CO. Using spatial and political data, this article assesses which factors are helpful in understanding precinct-level voter support for fracking bans.